Synergy and Collaboration in Strategies for Optimizing Bank Profitability: A Qualitative Study - Rahmat, Abmierdal; Nazaruddin, Nazaruddin; Perdana, Mirwan Surya (LifeSciFi, 2025)
This study aims to explore the role of synergy and collaboration in bank profitability optimization strategies, with a qualitative focus on branch leaders within the working area of the BRI Regional Office Padang. In-depth interview results reveal that cross-segment and inter-unit synergy and collaboration are strategic elements that form the foundation for addressing the increasingly complex dynamics of the banking industry. Synergy is understood as the alignment of direction and goals among work units, while collaboration is seen as the concrete implementation of integrated cooperation, such as joint canvassing, cross-segment customer referrals, and collective management of data pipelines/leads.These synergistic practices have been proven to enhance financial performance, including growth in Third-Party Funds (DPK), expansion of productive loans, reduction of Non-Performing Loans (NPL), and customer acquisition through local ecosystem development. However, the main challenges in implementation include sectoral egos, differing target segmentations, and siloed mindsets. Branch leaders address these challenges through motivational approaches, team-based reward systems, integration of collaborative Key Performance Indicators (KPIs), and support from digital infrastructure.These findings affirm that synergy and collaboration are not merely managerial complements but strategic foundations for creating sustainable profitability and enhancing customer satisfaction within BRI. The study also emphasizes that synergy and collaboration are not just operational tools, but organizational cultures that must be continuously nurtured to holistically support the bank’s profitability.